Psychosocial and Aesthetic Advantages of Reconstruction after Prophylactic Mastectomy: A Quality of Life and Aesthetic Analysis - Manahan, Michele A.; Baltodano, Pablo A.; Reinhardt, Myrna Eliann; Xie, Li; Muste, Justin C.; Tajamal, Rehan; Mohan, Raja; Flores, José M.; Drogt, Carolyn; Cooney, Carisa M.; Rosson, Gedge D. (Journal of Reconstructive Microsurgery, 2017)
Background Proper patient counseling regarding reconstruction after prophylactic mastectomy (PM) requires greater understanding of quality of life (QoL) and aesthetic outcomes. Our study evaluates these end points using the validated BREAST-Q and Garbay system.Methods We performed a retrospective chart review of 1,254 mastectomy patients (July 2008 through July 2012). Of those with completed preoperative BREAST-Q and reconstruction with a minimum of 6-month follow-up, 18 underwent bilateral PM (BPM), 36 underwent contralateral PM (CPM), and 30 matched controls were selected who underwent unilateral therapeutic mastectomy (TM) with contralateral symmetry procedure. Preoperative and 6-month postreconstruction BREAST-Q scores were compared within and between groups. Subsequently, aesthetic evaluation of 21 of a group of randomly selected reconstructions (7 TM, 7 CPM, and 7 BPM) was performed by 14 plastic surgery researchers. Potential correlations between aesthetic evaluations and QoL outcomes were examined.Results Demographic characteristics, preoperative satisfaction scores, and postoperative morbidity rates were similar among all three groups. Although reconstruction after BPM was associated with improved aesthetic outcomes (p < 0.001), a significant postoperative increase in satisfaction with breasts was noted only in the TM group (p = 0.006). CPM was associated with improved psychosocial well-being (p = 0.039) in our study. No further significant differences were noted.Conclusion Although BPM with reconstruction is associated with higher aesthetic outcomes compared with CPM or TM, QoL is not significantly increased. Reconstruction after CPM, but not BPM, is associated with increased psychosocial well-being. These valuable findings should be taken into account during preoperative counseling regarding elective PMs.
Keywords: prophylactic mastectomy; quality of life; psychosocial well-being